Cover Crop Species Composition Alters the Soil Bacterial Community in a Continuous Pepper Cropping System - Gao, Huan; Tian, Gangming; Khashi u Rahman, Muhammad; Wu, Fengzhi (Frontiers in Microbiology, 2022)
Cover crops can improve soil biological health and alter the composition of soil microbial communities in agricultural systems. However, the effects of diversified cover crops on soil microbial communities in continuous cropping systems is unclear. Here, using different soil biochemical analysis, quantitative PCR and 16S rRNA amplicon sequencing, we investigated the effects of cover crops, alone or in mixture, on soil physicochemical properties in 2019 and 2020, and soil bacterial communities in 2020 in a continuous pepper cropping system. A field trial was established before pepper planting and eight treatments were included: fallow (no cover crop) (CK); three sole cover crop treatments: wheat (Triticum aestivum L.) (W), faba bean (Vicia faba L.) (B), and wild rocket (Diplotaxis tenuifolia) (R); and four mixed treatments: wheat+wild rocket (WR), wheat+faba bean (WB), wild rocket+faba bean (RB), and wheat+wild rocket+faba bean (WRB). The pepper yield was increased in the WR and WB in 2019 and 2020, and in the WRB in 2020. Cover crops increased the soil pH, but decreased the concentrations of NH4+ and available phosphorus. Bacterial abundance was increased by cover crop treatments, and community structure was altered in the W, WB, and WRB treatments. Moreover, we found that pH was the key factor associated with the changes in the abundance and structure of the bacterial community. Cover crop treatments altered the bacterial community structure with shifts in the dominant genera, which have plant-growth-promoting and/or pathogen-antagonistic potentials, e.g., increased the abundances of Streptomyces, Arthrobacter and Bacillus spp. in the W and WRB, and Gaiella spp. in the WB. Overall, we found that cover crops altered the soil physicochemical properties and bacterial community, and these changes varied with species composition of the cover crops, with wheat and its combination with legumes as most effective treatments. These results suggest that the diversification within cover crops could provide better crop yield stimulatory affects by altering soil biochemical environment.